Implementation of Mobile Etle in Handling Traffic Violations by Two Wheeler Riders in Blitar City Police Office - Shafwan Jahri, Sultan; Wulandari, Monica Niken; Ramadan, Sardika Yusuf (Tanggon Kosala, 2024)
Currently, traffic problems in the Blitar City Police area are still ongoing. One of the problems faced is traffic violations committed by two-wheeled drivers, the most frequent violations each year. Law enforcement efforts by implementing electronic ticketing using ETLE Mobile are still not optimal in handling traffic violations by two-wheeled drivers. This study aims to describe the implementation, influencing factors, and optimization of ETLE Mobile in handling traffic violations by two-wheeled drivers at Polres Blitar City. The concepts used include optimization, traffic violations, and ETLE Mobile. The theories used include management theory, SWOT analysis, and legal effectiveness. This is a qualitative study with a field research type that takes data through interviews with several sources, observations, and document studies. The study results show that implementing ETLE Mobile at the Police Blitar City is one of the ticketing methods carried out by the Blitar City Police Traffic Unit. Various factors influence ETLE Mobile at the Blitar City Police that support and hinder its implementation, starting from the law that is the basis for implementation, law enforcement personnel who have undergone training, adequate infrastructure but still lacking in it, and the community and culture that tend to be conducive. Some of the obstacles in the implementation of ETLE Mobile are in the form of implementation planning that has not been well organized, minimal knowledge from the community about ETLE Mobile, and facilities that need to be improved to support the implementation of ETLE Mobile.